2022
DOI: 10.1021/jacs.1c12556
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Bandgap Perovskite Quantum Dots in Perovskite Matrix for Sky-Blue Light-Emitting Diodes

Abstract: The epitaxial growth of a perovskite matrix on quantum dots (QDs) has enabled the emergence of efficient red light-emitting diodes (LEDs) because it unites efficient charge transport with strong surface passivation. However, the synthesis of wide-band gap (E g) QD-in-matrix heterostructures has so far remained elusive in the case of sky-blue LEDs. Here, we developed CsPbBr3 QD-in-perovskite matrix solids that enable high luminescent efficiency and spectral stability with an optical E g of over 2.6 eV. We scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
99
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 41 publications
0
99
0
Order By: Relevance
“…[ 8–12 ] Recently, great breakthroughs have been achieved in the synthesis and performance of green‐ and red‐emitting PeQLEDs in recent years, [ 13–22 ] whereas the low performance of blue‐emitting PeQLEDs (wavelength range: 460–490 nm) impedes the development of commercial display applications for PeQLEDs. [ 23–27 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8–12 ] Recently, great breakthroughs have been achieved in the synthesis and performance of green‐ and red‐emitting PeQLEDs in recent years, [ 13–22 ] whereas the low performance of blue‐emitting PeQLEDs (wavelength range: 460–490 nm) impedes the development of commercial display applications for PeQLEDs. [ 23–27 ]…”
Section: Introductionmentioning
confidence: 99%
“…
performance of green-and red-emitting PeQLEDs in recent years, [13][14][15][16][17][18][19][20][21][22] whereas the low performance of blue-emitting PeQLEDs (wavelength range: 460-490 nm) impedes the development of commercial display applications for PeQLEDs. [23][24][25][26][27] The entire blue spectra are expected to be obtained by controlling the Br/Cl ratio in inorganic blue-emitting PeQDs (CsPb(Br x /Cl 1−x ) 3 ). [28] In contrast to defecttolerant CsPbI 3 and CsPbBr 3 QDs, deeper donor defects are easily created by halogen vacancies between the conduction band and valence band in CsPb(Br x /Cl 1−x ) 3 , which results in trapped excitons and non-radiative recombination, [29] limiting further improvement in the PLQY of the blue perovskite QDs.
…”
mentioning
confidence: 99%
“…Efficient and spectra-stable PeLEDs made from this material exhibited an EL maximum at 495 nm, an EQE of 13.8% and a maximum brightness exceeding 6000 cd m −2 . [71] By the way, Shen et al demonstrated that the improved performance of Ca 2+ doped CsPbI 3 NC PeLEDs exhibiting about threefold maximum EQE of 7.8% and 2.2-fold T 50 of 85 min, which could attribute to the decreased defect densities of films and reduced hole injection barrier. Figure 2i shows their EL stable peaks at 683 nm with a full width at half-maximum (FWHM) of 35 nm under various driving voltages.…”
Section: Less-lead Peledsmentioning
confidence: 99%
“…h) Schematic of Sr 2+ cations passivated by DFPPO, which offers strong binding and steric hindrance to block H 2 O. [ 71 ] Copyright 2022, ACS. i) EL spectra of Ca 2+ ‐doped CsPbI 3 NCs (0.40%) LEDs on various driving voltages and a photograph of the working device [inset in (i)].…”
Section: Development On Less‐lead and Lead‐free Peledsmentioning
confidence: 99%
See 1 more Smart Citation